2020
DOI: 10.3102/0013189x20940683
|View full text |Cite
|
Sign up to set email alerts
|

Education for a “Post-Truth” World: New Directions for Research and Practice

Abstract: In the so-called “post-truth” world, there exists widespread confusion and disagreement over what is known, how to know, and who to trust. Current education has largely failed to meet the challenges of this world. Grounded in a new analysis of the goals of epistemic education, we argue for new directions in instruction. Our analysis specifies three components of epistemic cognition that education should address: epistemic aims, ideals, and reliable processes. Apt epistemic performance of these components has f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 59 publications
1
61
0
8
Order By: Relevance
“…As stressed in prior research, the kind of classroom intervention found to be effective for promoting epistemic cognition often involves teachers' creating and supporting an open space where small groups of students can co-construct and challenge arguments about domain-specific problems [2,51]. Further, within the context of an open participation space, the type of task assigned to students may also influence their performance.…”
Section: Using Quality Talk Science (Qt S ) As a Potential Approach To Enhance Argumentation And Examine Epistemic Cognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…As stressed in prior research, the kind of classroom intervention found to be effective for promoting epistemic cognition often involves teachers' creating and supporting an open space where small groups of students can co-construct and challenge arguments about domain-specific problems [2,51]. Further, within the context of an open participation space, the type of task assigned to students may also influence their performance.…”
Section: Using Quality Talk Science (Qt S ) As a Potential Approach To Enhance Argumentation And Examine Epistemic Cognitionmentioning
confidence: 99%
“…Using the definition of apt epistemic performance, a process of elimination could have resulted in success (i.e., choosing the correct model), but it would not have necessarily been apt (i.e., choosing the correct model by providing reasons and evidence to support all aspects of the model). Therefore, to promote students' apt epistemic performance via scientific discourse [2], it is necessary to consider the model format for discussion and encourage students to negotiate ideas about scientific phenomena using normative practices in science.…”
Section: Rq2 Model Format and Explicit Instruction In Relation To Epistemic Cognition And Argumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, it’s challenging to adapt instruction to these new realities. In writing about teaching students to evaluate information in a “post-truth” world, Clark Chinn, Sarit Barzilai, and Ravit Golan Duncan (2020) argue for putting students in authentic learning environments in which they must navigate real-world complexity and ambiguity. They worry about the tendency to teach these skills in carefully scripted settings in which educators have more control but the opportunity for learning is modest.…”
Section: The Changing Purposes Of Us Schoolsmentioning
confidence: 99%
“…Sin embargo, también existen dificultades relacionadas con la baja calidad que tienen muchos documentos o lo contradictorios que pueden resultar entre sí (Greene & Yu, 2016). Adicionalmente, en nuestro tiempo se ha expandido el fenómeno de la 'posverdad', término que se utiliza para denotar un clima epistémico donde enunciados falsos aparecen en varios medios de comunicación y han conducido a las personas a dudar de las fuentes tradicionales de conocimiento (Chinn et al, 2020).…”
Section: Introductionunclassified